2021
DOI: 10.1186/s13256-021-02698-5
|View full text |Cite
|
Sign up to set email alerts
|

Neonates with coronavirus disease 2019 acquired from infected mothers: the incompatibility of maternal intensity and infant lung involvement: two case reports

Abstract: Background The outbreak of coronavirus disease 2019 (COVID-19) caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was declared a public health emergency by the World Health Organization on January 30, 2020. The results of recent studies have suggested that neonates may present symptoms of COVID-19. Although the presentation of the disease in neonates is known to vary, only a limited number of studies have investigated newborns infected with COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the third virus of the twenty-first century to become a global concern. 2 Qatar, a country that embraces a population of variable nationalities and ethnicities, was hit by the third wave of COVID-19 infection in early January 2022, the time at which the patient and her family in this case report acquired COVID-19 infection. Though the patient was not tested for the exact variant of COVID-19 virus, we know that 95% of the tested cases at that period were of Omicron variant.…”
Section: Discussionmentioning
confidence: 91%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the third virus of the twenty-first century to become a global concern. 2 Qatar, a country that embraces a population of variable nationalities and ethnicities, was hit by the third wave of COVID-19 infection in early January 2022, the time at which the patient and her family in this case report acquired COVID-19 infection. Though the patient was not tested for the exact variant of COVID-19 virus, we know that 95% of the tested cases at that period were of Omicron variant.…”
Section: Discussionmentioning
confidence: 91%
“…Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is the third virus of the twenty‐first century to become a global concern 2 . Qatar, a country that embraces a population of variable nationalities and ethnicities, was hit by the third wave of COVID‐19 infection in early January 2022, the time at which the patient and her family in this case report acquired COVID‐19 infection.…”
Section: Discussionmentioning
confidence: 93%
“…Newborns can also be infected with SARS‐CoV‐2 due to the immaturity of their immune systems; however, uncommon presentations have been associated with this age group 2 . In the few published cases of COVID‐19 in neonates, the presentation was that of late neonatal sepsis; interestingly, the lung involvement was not as common as in the older children and adults 7 …”
Section: Discussionmentioning
confidence: 99%
“…18 Another study reported two neonatal cases infected with COVID-19 who were born to mothers infected at the end of the third trimester of pregnancy. 19 In an Italian series comprising 22 women affected by COVID-19, Patanè et al identified two cases of mothers with a positive polymerase chain reaction (PCR) test who also were positive for SARS-CoV-2 in the placenta and in their neonates. 6 Another study showed the potential for intrauterine transmission of SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Though the first case was observed in China in December 2019, coronavirus disease 2019 (COVID- 19) was first identified in Turkey on the 9th of March 2020, later than many countries. 1 The rapid national and international spread of COVID-19 resulted in 240,260,449 cases with 4,890,424 deaths globally by October 19th 2021.…”
Section: Introductionmentioning
confidence: 99%